Book Review: Trihartono, A., Patriadi, H. B., & Hara, A. E. (2023). Gastrodiplomasi Indonesia. Pandiva. 300 pp. - Elvina Akyas Laksono Putri; Nino Viartasiwi (Universitas Wijaya Kusuma Surabaya, 2023)
In the study of international relations, Gastrodiplomacy emerges as a new and refreshing sub-study of diplomacy. Gastrodiplomacy explores the power and influence potencies of using food as a tool of culinary diplomacy (Chapple-Sokol, 2013). The term gastrodiplomacy was first mentioned by The Economist, a British weekly newspaper, on February 21, 2002. Gastrodiplomacy was first used to describe the efforts of the Thai government and diaspora to popularize its cuisine around the world (The Economist, 2002). Rockower (2014) suggests that gastrodiplomacy calls for the integration of diplomatic relationships and culture. Integration aims to shape the national image or perception of a country on the global stage. Suntikul (2019) explains that gastrodiplomacy shows the collective efforts of the government and non-state actors to enhance the country’s reputation overseas by exposing foreign tourists and visitors to their traditional cuisine. In substance, gastrodiplomacy tries to promote a country’s cuisines and culinary traditions to enhance trans-cultural understanding, boost their global image, and develop the country’s tourism and trade.Keywords: gastrodiplomacy; public diplomacy; Indonesia